Cost-effectiveness and quality of life of a diet intervention postpartum: 2-year results from a randomized controlled trial - Lars Hagberg; Anna Winkvist; Hilde K Brekke; Fredrik Bertz; Else Hellebö Johansson; Ena Huseinovic (BMC, 2019)
Abstract Background Pregnancy has been identified as a contributor to obesity. We have shown that a diet intervention postpartum produced a 2-y weight loss of 8%. Here, we present the impact of the diet intervention on cost-effectiveness and explore changes in quality of life (QOL). Methods A total of 110 postpartum women with overweight/obesity were randomly assigned to diet (D-group) or control (C-group). D-group received a 12-wk diet intervention within primary health care followed by monthly emails up to the 1-y follow-up. C-group received a brochure. Changes in QOL were measured using the 36-item Short Form Health Survey and EQ-5D. The analysis of cost-effectiveness was a cost-utility analysis with a health care perspective and included costs of intervention for stakeholder, quality-adjusted life-years (QALYs) gained and savings in health care. The likelihood of cost-effectiveness was examined using the net monetary benefit method. Results The D-group increased their QOL more than the C-group at 12 wk. and 1 y, with pronounced differences for the dimensions general health and mental health, and the mental component summary score (all p < 0.05). Cost per gained QALY was 1704-7889 USD. The likelihood for cost-effectiveness, based on a willingness to pay 50,000 USD per QALY, was 0.77-1.00. Conclusions A diet intervention that produced clinically relevant postpartum weight loss also resulted in increased QOL and was cost-effective. Trial registration Clinical trials, NCT01949558, 2013-09-24